The Role of Bhabinkamtibmas in Preventing the Crime of Child Abuse at the Tasikmalaya City Police Department - Liafani Karen (Advances in Police Science Research Journal, 2021)
The crime of sexual abuse against children at the Tasikmalaya City Police has increased over the last three years, this should not have happened because children are the next generation of the nation that should be protected. The Tasikmalaya City Police put forward preemptive measures to prevent criminal acts of sexual abuse against children carried out through programs that have been declared by the Tasikmalaya City Police. The purpose of this study was to describe the implementation of the prevention of criminal acts against children by the Bhabinkamtibmas at the Tasikmalaya City Police, to describe the role of the Bhabinkamtibmas at the Tasikmalaya City Police in preventing the crime of sexual immorality against children at the Tasikmalaya City Police and to find the factors that lead to the crime of sexual immorality. children at the Tasikmalaya City Police. In this study, the implementation of Bhabinkamtibmas duties in preventing criminal acts of sexual abuse against children using role theory, crime prevention theory and management theory. And by paying attention to its conformity with the concept of Community Policing. This research was conducted with a qualitative approach and the type of field research. With observation data collection techniques, interviews, and document study. The data analysis technique used includes data reduction, data presentation and drawing conclusions. The results of this research and the conclusions of this study indicate that based on the data obtained and interviews with the Head of Police, Head of Binmas, Kanit Binmas, Bhabinkamtibmas, Kanit PPA, perpetrators of criminal acts of child sexual abuse, and community leaders that members of Bhabinkamtibmas are still not thoroughly implementing the elements. management and the roles that are carried out have not been implemented evenly. The factors causing the crime of child sexual abuse are internal and external factors. Internal factors consist of psychological factors, biological factors and moral factors. Meanwhile, external factors include socio-cultural factors, social media, and the level of education.